2017
DOI: 10.1038/srep40121
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, distribution, and significance of transposable elements in the genome of the only selfing hermaphroditic vertebrate Kryptolebias marmoratus

Abstract: The Kryptolebias marmoratus is unique because it is the only self-fertilizing hermaphroditic vertebrate, known to date. It primarily reproduces by internal self-fertilization in a mixed ovary/testis gonad. Here, we report on a high-quality genome assembly for the K. marmoratus South Korea (SK) strain highlighting the diversity and distribution of transposable elements (TEs). We find that K. marmoratus genome maintains number and composition of TEs. This can be an important genomic attribute promoting genome re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 54 publications
2
34
1
Order By: Relevance
“…The most abundant repeat type was class II DNA transposons (19.89%), and a total of 32.4% repeat sequences were interspersed in the marine medaka genome. In comparison with the genomes of Japanese medaka (25.4%) and mangrove killifish Kryptolebias marmoratus (27%) (Rhee et al., ), the O. melastigma genome contained more repeat sequences. This could be one of the reasons why we kept obtaining low‐quality sequence reads.…”
Section: Resultsmentioning
confidence: 98%
“…The most abundant repeat type was class II DNA transposons (19.89%), and a total of 32.4% repeat sequences were interspersed in the marine medaka genome. In comparison with the genomes of Japanese medaka (25.4%) and mangrove killifish Kryptolebias marmoratus (27%) (Rhee et al., ), the O. melastigma genome contained more repeat sequences. This could be one of the reasons why we kept obtaining low‐quality sequence reads.…”
Section: Resultsmentioning
confidence: 98%
“…Using the annotated K. marmoratus reference genome (Rhee et al (2017), we identified the genomic context of the DMCs common to the two comparisons between hybrids and parental species, i.e. within gene body, promoter or intergenic region (Supplementary material).…”
Section: Genomic Context and Gene Ontology Enrichment Analysismentioning
confidence: 99%
“…The relationship between TEs and environmental conditions and the comprehension of involved mechanisms are representing an attractive challenge for the scientific community. Recently, besides to mixed mating strategy, a putative correlation between TE diversity and ecological pressure has been suggested to explain the high genetic diversity of Kryptolebias marmoratus (mangrove killifish) genome compared to other killifish species (Rhee et al 2017).…”
Section: The Relationship Between Tes and Environmental Conditionsmentioning
confidence: 99%